2018
DOI: 10.1089/pho.2017.4355
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Plasma Growth Factors (VEGF, PDGF, EGF, ANG1, and ANG2) in Patients with Varicose Veins Before and After Treatment with Endovenous Laser Ablation

Abstract: The altered plasma concentrations of growth factors VEGF, PDGF, EGF, ANG1, and ANG2 among patients with VVs normalized 1 week after treatment with EVLA compared with the control group. This may support the role of these factors in the pathogenesis of the disease. Future studies may evaluate if these changes can play a prognostic and/or predictive value regarding the adequacy of treatment and the possibility of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The concentrations of VEGF, a proangiogenic cytokine which promotes neovascularisation and increases vascular permeability, were found to be lower in the CVD group. Similar observations were made in a study comparing cytokine concentrations before and after endovenous laser ablation, where VEGF was found in lower concentrations in the blood of the patients before surgery [37]. In other studies, however, the concentrations of VEGF were higher in CVD patients: both in the venous tissue [22] and in the peripheral blood [36, 38].…”
Section: Resultssupporting
confidence: 79%
“…The concentrations of VEGF, a proangiogenic cytokine which promotes neovascularisation and increases vascular permeability, were found to be lower in the CVD group. Similar observations were made in a study comparing cytokine concentrations before and after endovenous laser ablation, where VEGF was found in lower concentrations in the blood of the patients before surgery [37]. In other studies, however, the concentrations of VEGF were higher in CVD patients: both in the venous tissue [22] and in the peripheral blood [36, 38].…”
Section: Resultssupporting
confidence: 79%
“…In patients with chronic venous disease, an elevated plasma levels of VEGF was revealed, which increased with disease severity 19 41. Some studies demonstrated altered plasma/serum concentration of VEGF among patients with varicose veins before and postoperative, and it may support its role in the pathogenesis of disease 4244. However, the evaluation of studied factor in tissue is of particular importance, because VEGF plasma level does not reflect its role in the pathogenesis of the disease 18 41.…”
Section: Discussionmentioning
confidence: 99%
“…19 41 Some studies demonstrated altered plasma/ serum concentration of VEGF among patients with varicose veins before and postoperative, and it may support its role in the pathogenesis of disease. [42][43][44] However, the evaluation of studied factor in tissue is of particular importance, because VEGF plasma level does not reflect its role in the pathogenesis of the disease. 18 41 In the present study, we demonstrated increased VEGF-A content in varicose veins in comparison with the normal vein wall.…”
Section: Original Researchmentioning
confidence: 99%
“…In addition, EGF has been indicated to contribute to the permeability of ECs and vascular tube formation, in particular, inducing endothelial cadherin tyrosine phosphorylation (6,13,60,68). Furthermore, both EGF and VEGF belong to the class of plasma growth factors; the expression of EGF and VEGF or their receptors is closely associated with atherosclerotic or other vascular diseases (2,47,72). It has also been reported that VEGF could upregulate the expression of EGF receptors (EGFRs); many inhibitors could block both EGFRs and VEGF receptors (VEGFRs), and there appears to be cross-talk between EGFR and VEGFR pathways (24,31,36,41,51,65).…”
Section: Introductionmentioning
confidence: 99%